Protein tyrosine phosphatase 1B negatively regulates S100A9-mediated lung damage during respiratory syncytial virus exacerbations - Foronjy, R.F.; Ochieng, P.O.; Salathe, M.A.; Dabo, A.J.; Eden, E.; Baumlin, N.; Cummins, N.; Barik, S.; Campos, M.; Thorp, E.B.; Geraghty, P. (Mucosal immunology, 2016)
Protein tyrosine phosphatase 1B (PTP1B) has anti-inflammatory potential but PTP1B responses are desensitized in the lung by prolonged cigarette smoke exposure. Here we investigate whether PTP1B expression affects lung disease severity during respiratory syncytial viral (RSV) exacerbations of chronic obstructive pulmonary disease (COPD). Ptp1b−/− mice infected with RSV exhibit exaggerated immune cell infiltration, damaged epithelial cell barriers, cytokine production, and increased apoptosis. Elevated expression of S100A9, a damage-associated molecular pattern molecule, was observed in the lungs of Ptp1b−/− mice during RSV infection. Utilizing a neutralizing anti-S100A9 IgG antibody, it was determined that extracellular S100A9 signaling significantly affects lung damage during RSV infection. Preexposure to cigarette smoke desensitized PTP1B activity that coincided with enhanced S100A9 secretion and inflammation in wild-type animals during RSV infection. S100A9 levels in human bronchoalveolar lavage fluid had an inverse relationship with lung function in healthy subjects, smokers, and COPD subjects. Fully differentiated human bronchial epithelial cells isolated from COPD donors cultured at the air liquid interface secreted more S100A9 than cells from healthy donors or smokers following RSV infection. Together, these findings show that reduced PTP1B responses contribute to disease symptoms in part by enhancing S100A9 expression during viral-associated COPD exacerbations.